Productivity estimation of cutter suction dredger operation through data mining and learning from real-time big data. Issue 7 (25th January 2021) - Fu, Jiake; Tian, Huijing; Song, Lingguang; Li, Mingchao; Bai, Shuo; Ren, Qiubing
Abstract : Purpose: This paper presents a new approach of productivity estimation of cutter suction dredger operation through data mining and learning from real-time big data. Design/methodology/approach: The paper used big data, data mining and machine learning techniques to extract features of cutter suction dredgers (CSD) for predicting its productivity. ElasticNet-SVR (Elastic Net-Support Vector Machine) method is used to filter the original monitoring data. Along with the actual working conditions of CSD, 15 features were selected. Then, a box plot was used to clean the corresponding data by filtering out outliers. Finally, four algorithms, namely SVR (Support Vector Regression), XGBoost (Extreme Gradient Boosting), LSTM (Long-Short Term Memory Network) and BP (Back Propagation) Neural Network, were used for modeling and testing. Findings: The paper provided a comprehensive forecasting framework for productivity estimation including feature selection, data processing and model evaluation. The optimal coefficient of determination ( R 2 ) of four algorithms were all above 80.0%, indicating that the features selected were representative. Finally, the BP neural network model coupled with the SVR model was selected as the final model. Originality/value: Machine-learning algorithm incorporating domain expert judgments was used to select predictive features. The final optimal coefficient of determination ( R 2 ) of the coupled model of BP neural network and SVR is 87.6%, indicating that the method proposed in this paper is effective for CSD productivity estimation.